2019
DOI: 10.3171/2018.1.jns171774
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of flow diversion with clipping and coiling for the treatment of paraclinoid aneurysms in 115 patients

Abstract: OBJECTIVE Paraclinoid aneurysms represent approximately 5% of intracranial aneurysms (Drake et al. [1968]). Visual impairment, which occurs in 16%-40% of patients, is among the most common presentations of these aneurysms (Day [1990], Lai and Morgan [2013], Sahlein et al. [2015], and Silva et al. [2017]). Flow-diverting stents, such as the Pipeline Embolization Device (PED), are increasingly used to treat these aneurysms, in part because of their theoretical reduction of mass effect (Fiorella et al. [2009]). L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 45 publications
(60 reference statements)
1
30
0
2
Order By: Relevance
“…Previous studies have revealed the feasibility and safety of using only a PED without coils. These studies indicate that the PED can effectively divert blood flow from large or giant aneurysms and can shrink the sac size during thrombosis, relieving the mass effect and even resolving the compressional symptoms (8, 9, 18). However, use of a PED alone may increase the risk of rupture after the intervention, especially for large or giant aneurysms, because the occlusion occurs over a delayed period (11, 12).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Previous studies have revealed the feasibility and safety of using only a PED without coils. These studies indicate that the PED can effectively divert blood flow from large or giant aneurysms and can shrink the sac size during thrombosis, relieving the mass effect and even resolving the compressional symptoms (8, 9, 18). However, use of a PED alone may increase the risk of rupture after the intervention, especially for large or giant aneurysms, because the occlusion occurs over a delayed period (11, 12).…”
Section: Discussionmentioning
confidence: 89%
“…The Pipeline embolization device (PED; ev3 Neurovascular, Irvine, CA, USA), which is one of the FDs that has been approved by the Food and Drug Administration, is the most commonly used FD at our center. Because of the excellent flow diverting force, the quantity of coils can be decreased during the intervention, making it possible to reduce the size of the aneurysm; the aneurysm may thus physically shrink by avoiding dense packing of the coil in the aneurysm (69). Numerous studies have revealed shrinkage of aneurysms and recovery of compressive cranial nerve symptoms following PED placement in cerebral aneurysms; however, almost all of these studies involved the use of a PED without coils (79).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow diverters now dominate the treatment of cavernous and paraclinoidal internal carotid artery (ICA) aneurysms, and off-label use extends beyond the supraclinoid ICA. 15,61 Intra-aneurysmal flow diverters have been developed for bifurcation aneurysms. 3 What remains for microsurgery are complex aneurysms, defined as those with wide necks, large size, dolichoectatic morphology, intraluminal thrombus, previous endovascular therapy, or atherosclerotic walls.…”
Section: Decline Of Aneurysm Surgerymentioning
confidence: 99%
“…However, newer endovascular techniques using flow diverters and pipeline embolisation device have shown promising results in terms of improvement of visual symptoms, obliteration rate, complications and recurrence and may play a greater role in future in treatment of paraclinoid aneurysms [8]. However, financial constraints and availability of infrastructure for coiling will continue to be a major hurdle for these endovascular techniques particularly in developing countries around the world.…”
Section: Endovascular Treatment Is Not Available At Presentmentioning
confidence: 99%